A mixed-methods evaluation of the Educational Supervision Agreement for Wales. Issue 6 (8th June 2017) - Webb, Katie Louise; Bullock, Alison; Groves, Caroline; Saayman, Anton Gerhard
Abstract : Objectives: In a bid to promote high-quality postgraduate education and training and support the General Medical Council's (GMC) implementation plan for trainer recognition, the Wales Deanery developed the Educational Supervision Agreement (EdSA). This is a three-way agreement between Educational Supervisors, Local Education Providers and the Wales Deanery which clarifies roles, responsibilities and expectations for all. This paper reports on the formative evaluation of the EdSA after 1 year. Design: Evaluation of pan-Wales EdSA roll-out (2013–2015) employed a mixed-methods approach: questionnaires (n=191), interviews (n=11) with educational supervisors and discussion with key stakeholders (GMC, All-Wales Trainer Recognition Group, Clinical Directors). Numerical data were analysed in SPSS V.20; open comments underwent thematic content analysis. Participants: The study involved Educational Supervisors working in different specialties across Wales, UK. Results: At the point of data collection, survey respondents represented 14% of signed agreements. Respondents believed the Agreement professionalises the Educational Supervisor role (85%, n=159 agreed), increases the accountability of Educational Supervisors (87%; n=160) and health boards (72%, n=131), provides leverage to negotiate supporting professional activities' (SPA) time (76%, n=142) and continuing professional development (CPD) activities (71%, n=131). Factor analysis identified three principal factors: professionalisation of the educational supervisor role, supporting practice through training and feedback and implementation of the Agreement. Conclusions: Our evidence suggests that respondents believed the Agreement would professionalise and support their Educational Supervisor role. Respondents showed enthusiasm for the Agreement and its role in maintaining high standards of training.